Analyzing the Impact of Artificial Intelligence (AI) Technology on the Implementation of Clean and Healthy Living Behaviors (PHBS) in Madrasah Aliyah Negeri Schools, Binjai City - Nia Astuti; Tri Niswati Utami; Asriwati Asriwati (Journal of Innovative and Creativity, 2025)
This study explores the influence of Artificial Intelligence (AI) technology on the implementation of Clean and Healthy Living Behavior (PHBS) among high school students at Madrasah Aliyah Negeri (MAN) Kota Binjai. Utilizing a quantitative cross-sectional design, data were collected through structured questionnaires from 72 Grade XI students selected via cluster random sampling. The analysis employed univariate, bivariate (Chi-square), and multivariate (logistic regression) techniques to identify the most significant influencing factors. The results show that knowledge, attitude, infrastructure, and teacher support all significantly affect students’ PHBS implementation. Among these, student knowledge emerged as the most dominant factor. Although infrastructure had a significant relationship, its influence was less pronounced compared to human-centered variables such as knowledge and teacher support. These findings suggest that AI integration in health education is most effective when supported by student understanding and active teacher involvement. The study contributes to the growing body of evidence supporting AI-assisted behavioral interventions in schools and highlights the need for a holistic, knowledge-driven approach in implementing digital health programs.